Matematické modely v logistice - Nevrlý, Vlastimír (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Cílem práce je modelovat dopravní sítě s charakterem podobným reálným sítím a analyzovat závislost výpočtové náročnosti na velikosti sítě pomocí testovacích výpočtů na původním optimalizačním modelu pro podporu koncepčních rozhodnutí v oblasti odpadového hospodářství nazývaného NERUDA. Tyto výpočty jsou provedeny na základě znalosti modelu NERUDA. Výsledky jsou následně zpracovány a patřičně vyhodnoceny.

The aim of the bachelor thesis is to model and generate test transportation networks, which are similar to real-world waste management networks. Several software tools (Mathematica, GAMS, Excel, VBA) are used to develop suitable procedures. The next task is to analyze dependence of computational complexity on the size of network by using statistical test computations. The existing original optimization model called NERUDA that supports decision-making in the eld of waste management is utilized. The obtained results are processed, analysed and interpreted in detail.
Mathematical models in logistics
Keywords: dopravní síť; generování; kostra; teorie grafů; hrany; uzly; model; výpočtová náročnost; transportation network; generation; spanning tree; graph theory; edges; vertices; model; computational complexity